2002
DOI: 10.1111/j.1468-2885.2002.tb00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Theory of Family Communication

Abstract: In this article, the authors develop a theory of family communication that is based on the schematic representation of relational knowledge. They discuss pertinent issues surrounding family communication and develop a general model of the role of relational schemas for interpersonal communication. Taking the specific environment of family communication into consideration, the authors then develop a theory of family communication based on a family relationship schema and describe the schema's location in cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
230
0
17

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(258 citation statements)
references
References 20 publications
11
230
0
17
Order By: Relevance
“…The attacking behaviors may be adolescents' contributions to an overall hostile and coercive family context (Dishion et al 1992; see also, Davis et al 2002). Through coercive interactions with parents, adolescents may development a negative interpersonal schema that makes it likely they will use attacking reactions in interpersonal relationships especially those with parents (Koerner and Fitzpatrick 2002).…”
Section: Discussionmentioning
confidence: 98%
“…The attacking behaviors may be adolescents' contributions to an overall hostile and coercive family context (Dishion et al 1992; see also, Davis et al 2002). Through coercive interactions with parents, adolescents may development a negative interpersonal schema that makes it likely they will use attacking reactions in interpersonal relationships especially those with parents (Koerner and Fitzpatrick 2002).…”
Section: Discussionmentioning
confidence: 98%
“…By contrast, communication problems are characterized by criticism and distrust, and show similarities to controlling behavior strategies. In a similar vein, Koerner and Fitzpatrick (2002) describe two significant aspects of family communication-conversation-orientation and conformity-orientation-that overlap with autonomy-supportive and controlling behavior. Conversation orientation represents the openness of family communication across a wide range of topics.…”
Section: Introductionmentioning
confidence: 94%
“…In line with SDT, both communication research (Barnes and Olson 1985;Olson 2000) and family psychology research (Koerner and Fitzpatrick 2002) highlight the importance of verbal interchange on equal footing between parents and children. In Barnes and Olson's Circumplex Model of Family Relationships (1985), communication between family members is assigned an important function.…”
Section: Introductionmentioning
confidence: 96%
“…This scale is introduced by Fitzpatrick et al (12) and has 26 items on a Likert scale from four (completely agree) to zero (completely disagree). This scale measures 2 subscales; conformity orientation by 11 items (sample item: my parents feel that is important to be boss) and conversation orientation by 15 , and examined the construct validity using the factor analysis and internal consistency. The criterion validity test showed that there is an acceptable correlation between RFCP and PBI.…”
Section: Revised Family Communication Patternsmentioning
confidence: 99%
“…(14). However, in the conformity orientation aspects, the emphasis is on interdependency and continuity of the family members and they are put under pressure to equalize their attitudes, values and beliefs (15). Studies show that each of these orientations can have its own certain consequences.…”
Section: Introductionmentioning
confidence: 99%